استخدام الصور المتحركة لتنمية قدرة التلاميذ على الحوار العربي - Miswarul Abdi Aziz (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
his study aims to investigate students' responses to the use of animated images in teaching Arabic dialogue and to evaluate the effectiveness of using animated images in developing students' ability to engage in Arabic dialogue. The research method employed by the researcher is the action research method. The data collection methods used in this research include observation, questionnaires, tests, and documents. The research findings indicate that students have a great interest in learning conversation, and they showed enthusiasm and significant engagement during the learning process. Animated images help students to better understand educational materials. They also encourage active participation in small groups, which increases their interaction and discussions about the material. This teamwork fosters the exchange of ideas and learning strategies, making the learning process enjoyable rather than boring. Furthermore, the presence of healthy competition in the animated images motivates students to participate and achieve good results. The use of animated images enhances students' ability to engage in Arabic dialogue, and the education is effective based on the test result, where the calculated T-value is 2.115, which is greater than the table T-value of 2.007 at a degree of freedom (df 51) and a significance level of 0.05. Therefore, the researcher concludes that the application of animated images is an effective and impactful tool in improving students' performance in mastering Arabic dialogue.